Geographic information of fish-borne parasitic metacercaria in chi river, Mahasarakham, Thailand - C. Nithikathkul (2018)
Fish-borne infections continue to be a major public health problem, with more than 50 million people infected throughout the world. Fish-borne parasites of humans and animals, are dorso-ventrally flattened and hermaphroditic and require one or more intermediate hosts. Fish-borne trematodes have been found in the small intestines of several definitive hosts such as birds, cats, dogs, rats and humans. These hosts were infected by eating raw freshwater fish containing encysted metacercariae. Thus, this study was proposed to urgently investigate the geographic information for the prevalence of fish-borne trematode metacercariae in 10 freshwater stations in the Chi river area in Mahasarakham province of Thailand. Four hundred and twenty samples offreshwater fish from 19 different species were randomly collected and examined for fish-borne trematode metacercaria. The fish were found infected with 3 fish-borne trematode metacercariae, namely; Opisthorchis viverrini, Haplorchis taichui, and Haplorchoides species. The prevalence of fish-borne metacercariae was 28.33% (119/420), Opisthrochis viverrini 1.67% (7/420) and the intensity of metacercaria was 0.80 per fish. Our study shows that fish-borne trematode metacercariae are found in a variety of fish species, relating to Opisthorchis viverrini, H. taichui, and Haplorchoides sp. The geographic information (latitude and longitude) associated with the infection rates among susceptible species of fresh water fish was recorded and built a fish-borne geo-dataset for Geographical Information System (GIS) development. GIS can be useful in establishing strategies for the prevention of transmission of food borne diseases originating in infected fish found in water catchment areas. © Geoinformatics International.